Judicial process in America - Carp, Robert A. (New Delhi, 2014)
Known for shedding light on the link between the courts, public policy, and the political environment, the new ninth edition of Judicial Process in America provides a comprehensive overview of the American judiciary.
Keywords: "Justice, Administration of-United States"